A Review of Eggshell Powder and Fly Ash-Based Geopolymers Concrete - I.C. Moison; Lillian Gungat; Hidayati Asrah; F.H. Chiew (2022)
This is a review of the current research on the development of geopolymer based of eggshell powder (ESP) and fly ash (FA). This paper observes the mechanical properties which are the compressive strength and tensile strength of eggshell powder (ESP) and fly ash (FA) based geopolymer that is formed by an alkali activation method. It is shown that the mechanical properties of alkaline activated geopolymer is significantly affected by its proportion of raw material in concrete; specifically, the fly ash (FA) to eggshell powder (ESP) ratio and the alkali activator ratio. Moreover, it is shown that curing temperature also may be a very influential factor towards the mechanical properties of the concrete. However, more experimental studies are required for eggshell powder (ESP) and fly ash (FA) based geopolymer as there are not many studies yet in this field have been conducted till date.